TONER INK USED IN LASER PRINTER AND COPIER MACHINES POSES TOXIC EFFECTS ON DEVELOPMENTAL STAGES OF Sarcophaga ruficornis Fabricius (Diptera: Sarcophagidae) - SINGH, ZORAWAR; SINGH, AMANDEEP; KAUR, MANVEEN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Printer toner is used in laser printers and photocopiers for printing text and images. Carbon powder and iron oxide are the main constituents of printer toner which are further mixed with different polymers in order to improve printing quality. Several engineered nanomaterials present in toner ink are released during the process of printing that have several adverse health effects. In the present study, we investigated toxicity of printer toner on the developmental stages of Sarcophaga ruficornis Fabricius (Diptera: Sarcophagidae). The fly was reared on goat flesh in the lab and 3rd instar larvae were exposed to four different concentrations of printer toner (10, 100, 1000 and 10000 ppm). Following exposure, larval mortality, pupation, pupal mortality and adult emergence were recorded. The results revealed a dose dependent toxic effect on developmental stages of S. ruficornis at tested concentrations. Further studies are recommended to test the toxicity of printer ink on different animal models so as improve the understanding towards its mechanisms involved in different health implications.